Screwed and cement implant prosthesis: current clinical considerations - Bruna Palmeira COSTA; Julliana Cariry Palhano FREIRE; Waleska Ohana de Souza MELO; Ernani Canuto FIGUEIRÊDO JÚNIOR; Eduardo Dias RIBEIRO; Jozinete Vieira PEREIRA (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT Introduction: There is no consensus as to which cemented or screwed retention system is best to avoid bone loss around the implant from a fixed implant-supported restoration. Objective: To evaluate the prosthesis retention systems on screw and cemented implants, regarding: bone loss, survival and failure rate, biological complications and microbiological analysis. Methods: A search was made for scientific articles that contemplated the subject through the databases Pubmed and SciELO, without period restriction. The titles, abstracts and then access to the full text has been verified. Results: It was found that excess cement may play an important role in the development of peri-implant disease. Technical failures are most seen in prosthesis retained by screws, and biological complications in cemented crowns. The success rate for both restraint systems is high, and retention-independent implant prosthesis treatment provides predictability. Conclusion: The appropriate retention system for the patient depends on several factors, including indication, advantages and disadvantages, retention provided, aesthetics and clinical performance.